如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]18039c885d99cae.jpg[/img]
A: 101
B: 011
C: 110
D: 111
A: 101
B: 011
C: 110
D: 111
B
举一反三
- 如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]1803a2a51c33118.jpg[/img] A: 101 B: 011 C: 110 D: 111
- 如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]1803c60f2218663.jpg[/img] A: 101 B: 011 C: 110 D: 111
- 如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]1803072091d0898.jpg[/img] A: 101 B: 011 C: 110 D: 111
- 如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]17de61bda746799.jpg[/img] A: 101 B: 011 C: 110 D: 111
- 如下图所示,输出F为1,A、B、C的取值应为 。[img=246x115]18030149b3b7254.jpg[/img] A: 101 B: 011 C: 110 D: 111
内容
- 0
如下图所示,输出F为1,A、B、C的取值应为( )?[img=1242x564]17de8ede1c76090.png[/img] A: 101 B: 011 C: 110 D: 111
- 1
如下图所示,输出F为1,A、B、C的取值应为。[img=270x113]17e0bd5b53ae2ed.png[/img] A: 101 B: 011 C: 110 D: 111
- 2
如下图所示,输出F为1,A、B、C的取值应为( )?[img=1242x564]18033cdfd25d9cc.png[/img] A: 101 B: 011 C: 110 D: 111
- 3
使函数[img=228x67]17e0abb8825558a.png[/img]为1的变量取值是? A: 001 B: 101 C: 011 D: 111
- 4
使逻辑函数[img=532x111]17da6dd11bbce29.png[/img]为1的变量取值是( )。 A: 111 B: 001 C: 101 D: 011